Handbook of research on global aspects of sustainable finance in times of crises - Gok, Ibrahim Yasar, 1985- (Advances in finance, accounting, and economics (AFAE) book series., 2022)
"This book, with its theoretical and empirical perspectives, discusses contemporary issues regarding sustainable finance in light of crises especially the Covid-19 pandemic and the climate crisis"--